Fit Minded College Edition Pilot Study: Can a Magazine-Based Discussion Group Improve Physical Activity in Female College Freshmen?. Issue 1 (January 2017) - Pellitteri, Katelyn; Huberty, Jennifer; Ehlers, Diane; Bruening, Meg
Abstract : Objective: Initial efficacy of a magazine-based discussion group for improving physical activity (PA), self-worth, and eating behaviors in female college freshmen. Design: Randomized control trial. Setting: A large university in southwestern United States. Participants: Thirty-seven female college freshmen were randomized to the intervention (n = 17) and control groups (n = 20) in September 2013. Intervention: Participants completed an 8-week magazine-based discussion group program, Fit Minded College Edition, adapted from Fit Minded, a previously tested theory-based intervention. Education on PA, self-worth, and nutrition was provided using excerpts from women's health magazines. Participants also had access to a Web site with supplementary health and wellness material. The control group did not attend meetings or have access to the Web site but received the magazines. Interventions focusing on concepts of self-worth with less focus on weight and appearance may promote long term PA participation and healthy eating behaviors in college women. Main Outcome Measures: Self-reported PA, global self-worth, knowledge self-worth, self-efficacy, social support, eating behaviors (ie, fruit/veggie/junk food/sugar-sweetened beverage consumption), satisfaction, and Web site usage. Results: Mean age of participants was 18.11 (SD = 0.32) years. Time × Intervention effects were observed for PA minutes per week (Partial η 2 = 0.34), knowledge self-worth (Partial η 2 = 0.02), and daily sugar-sweetened beverage consumption (Partial η 2 = 0.17) ( P < .05), with the intervention group reporting greater increases in PA and knowledge self-worth and greater decreases in sugar-sweetened beverage consumption. Conclusions: A magazine-based discussion group may provide a promising platform to improve health behaviors in female college freshmen.